2023
DOI: 10.1186/s10194-023-01696-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of pharmacological interventions for managing chronic migraine in adults: a systematic review and network meta-analysis

Seyran Naghdi,
Martin Underwood,
Jason Madan
et al.

Abstract: Background Chronic migraine can be a profoundly disabling disorder that may be treated with preventive medications. However, uncertainty remains as to which preventive medication is the most effective. We present a network meta-analysis to determine the effectiveness and rank of preventive drugs for chronic migraine in adults. Methods We identified, reviewed, and extracted data from randomised controlled trials (RCTs) of preventive drugs for chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Since each of the drugs work through different pathways it is plausible that more substantial effects could be achieved through combinations. Our literature reviews found modest effect sizes, the smallest being 1.49 fewer monthly migraine days for topiramate, and the largest being 2.77 fewer migraine days per month for Fremanezumab 5 . Effect sizes describe the whole population, including those who did not respond to a medication at all, and so the effect on an individual can be much higher.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Since each of the drugs work through different pathways it is plausible that more substantial effects could be achieved through combinations. Our literature reviews found modest effect sizes, the smallest being 1.49 fewer monthly migraine days for topiramate, and the largest being 2.77 fewer migraine days per month for Fremanezumab 5 . Effect sizes describe the whole population, including those who did not respond to a medication at all, and so the effect on an individual can be much higher.…”
Section: Discussionmentioning
confidence: 55%
“…Our 2023 systematic review found that further definitive evidence is needed on many commonly prescribed medications (e.g. amitriptyline, Candesartan, propranolol) [5][6][7] . However, no work exists to guide researchers and funders designing and commissioning research in terms of the priorities of patients and healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic headache disorders can be profoundly disabling. In comparison to the substantial amount of research on the biological mechanisms of chronic headache disorders, and success in finding drug treatments of proven benefit for chronic migraine [ 1 ], there has been rather less focus on, and less success with, treatments addressing the social and psychological components of the disability caused by chronic headache disorders [ 2 ]. The international classification of headache disorders does not recognise the disorder of ‘chronic headache’ as a distinct disorder.…”
Section: Introductionmentioning
confidence: 99%
“…CGRP is a 37-amino acid peptide expressed in a significant proportion of trigeminal primary sensory neurons; it can be Cells 2024, 13, 653 2 of 18 demonstrated to be present in cerebral and meningeal sensory nerves and is also abundantly expressed throughout the central nervous system [7,8]. Increased levels of CGRP are highly associated with headache disorders such as migraines; the importance of CGRP in pain-related research became obvious following the introduction of CGRP antagonists as antimigraine pharmaceuticals [9,10]. The CGRP-release and the consequent dilation of meningeal and cerebral blood vessels are involved in the regulation of cerebral blood flow, showcasing its importance in certain pathological conditions such as ischemia and SAH [11,12].…”
Section: Introductionmentioning
confidence: 99%